A novel orthotopic animal model of human chondrosarcoma - Horas, K.; Kurth, A. A.; Tonak, M. (Osteologie, 2012)
Chondrosarcoma is the second most common primary malignant bone tumour in humans. Currently, surgical resection is the only appropriate curative approach as it is relatively unresponsive to traditional chemoand radiotherapy. However, a complete resection is often hindered due to the proximity to organs resulting in a poor outcome of this challenging malignancy. Few novel antitumour agents have been tested on different chondrosarcoma cell lines in vitro so far. In order to qualify new agents in vivo, animal models are often used in which cell lines are subcutaneously injected prior to chemotherapeutical treatment. These types of models often lack relevance to the human chondrosarcoma as the number of agents that fail in the clinic far outweighs those considered effective on in vivo studies. Orthotopic xenograft models however are of much more predictive value. Thus, the development of a novel orthotopic animal model for human chondrosarcoma using a three-dimensional matrix carrying tumour cells, was the aim of this study. For that purpose, SW-1353, a human bone chondrosarcoma cell line, was first cultured in MatrigelTM, followed by orthotopic implantation into10 SCID mice by intra-tibial injection. After 40 days, the animals developed localized bone tumours verified by radiographic and histological examinations. Radiologic and histological sections showed osteolysis and invasive tumour growth. This study demonstrates a promising new method for effective and reproducible orthotopic implantation of human chondrosarcoma. The presented animal model allows further examination and can be used as a predictive preclinical model for anticancer drug activity in humans.
Keywords: Chondrosarcoma; orthotopic; xenograft; primary malignant bone tumour; animal model